Young Spanish People’s Gendered Representations of People Working in STEM. A Qualitative Study - Sáinz, Milagros; Martínez-Cantos, José-Luis; Rodó-de-Zárate, María; Romano, María José; Arroyo, Lidia; Fàbregues, Sergi (Frontiers in Psychology, 2019)
The present qualitative study analyzes how a group of young people already involved in STEM fields perceive the prototypical person working in STEM. Gender differences between participants in technological and non-technological STEM fields were analyzed. A total of 27 young people (59.3% women) took part in the interviews (Mean Age=25.48 years). Of them, 16 participants were working in STEM professions, and 11 were enrolled in the final courses of STEM degrees. The results of the content analysis were examined in light of social role theory and the multidimensional structure of gender stereotypes. Men in these fields were therefore attributed an unappealing and weird physical appearance. Some female participants linked STEM professionals’ intellectual abilities to the stereotype that men have higher abilities in these fields. Whereas females attributed effort and perseverance to STEM professionals’ intellectual aptitudes, males referred to the development of soft skills. Participants in technological STEM fields connected the stereotype of being a ‘weirdo’ to a boring job, whereas those in non-technological fields linked it to their unconventional character. Some participants were disappointed by a lack of correspondence between expectations and the actual job STEM professionals do. Moreover, females in technological STEM fields commented on the job’s low social impact, while males mentioned low attainment of technical qualifications. Most referents in STEM fields were masculine, some of whom were present in the mass media. The practical implications of the findings are discussed.